Про лінійну та квадратичну двоетапні транспортні задачі - Стецюк, П.І.; Лиховид, О.П.; Супрун, А.А. (Кібернетика та комп’ютерні технології, 2020)
Робота присвячена математичним моделям двоетапної транспортної задачі та до-статньо універсальному способу їх розв'я-зання за допомогою сучасного програмного забезпечення. Описано формулювання двое-тапної транспортної задачі та наведено її властивості, наведено опис задачі на мові моделювання AMPL та результати розра-хунків для тестового прикладу, описано ква-дратичну двоетапну транспортну задачу та доведено єдиність її розв'язку. The purpose of the article is to propose the use of AMPL code for solving a linear programming two-stage transportation problem using modern software for linear programming problems, to formulate a mathe-matical model of a quadratic programming two-stage transportation problem and to investigate its properties. Results. The properties of two variants of a two-stage transportation problem are described: a linear pro-gramming problem and a quadratic programming problem. An AMPL code for solving a linear programming two-stage transportation problem using modern software for linear programming problems is given. The results of the calculation using Gurobi program for a linear programming two-stage transportation problem, which has many solutions, are presented and analyzed. A quadratic programming two-stage transportation problem was formulated and conditions were found under which it has unique solution.